TAFSIR AYAT AL-QUR’AN TENTANG POTENSI-POTENSI ATAU KEUNGGULAN MANUSIA YANG PERLU DIKEMBANGKAN LEWAT PENDIDIKAN [QS. AL-BAQARAH/2: 30-39] - Arman; Uswatul Hasana; Apri Muliana; Sulkifli; Yuliani (Al Arsy: Journal of Education, Management and Islamic Thought, 2026)
This study aims to examine the human potentials that need to be developed through education based on the interpretation of Qur'an Surah Al-Baqarah verses 30–39. These verses explain the creation of human beings as vicegerents (khalifah) on earth who are endowed with various advantages, such as intellectual ability, knowledge acquisition, moral awareness, and responsibility toward life. This research employs a library research method with a descriptive qualitative approach through the analysis of Qur'anic verses, classical and contemporary tafsir literature, books, and relevant scholarly journals. The findings reveal that human beings possess intellectual, spiritual, moral, and social potentials that serve as the primary foundation for carrying out their role as Allah’s vicegerents on earth. These potentials should be nurtured and developed through education that emphasizes knowledge acquisition, character building, and faith development. Islamic education plays a crucial role in optimizing human nature (fitrah) so that individuals can become morally upright, responsible, and capable of making positive contributions to society. Therefore, the development of human potential through education is an essential effort to fulfill the purpose of human creation as both servants of Allah and His vicegerents on earth.